(untitled) (Marketing Journal, 2025)
The article scientifically analyzes the effectiveness of the integrated application of digital marketing tools – SEO, SMM, influencer marketing, chatbots, and web analytics – in attracting students to higher education institutions in Uzbekistan. Similar to how digital technologies have become a key factor in enhancing efficiency in the healthcare sector, student recruitment in higher education is also viewed as a business process. This process involves managing the applicantʼs continuous journey from awaren ess to admission and enrollment through digital platforms. Such an approach № 10-SON OKTA BR, 2025 -YIL 363 contributes to improving international competitiveness, student experience, and management cost optimization, thereby increasing the overall efficiency of higher education institutions.